2013
DOI: 10.1177/1933719113492204
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of the Interleukin 1 System in Pregnancy and Labor

Abstract: This work assessed the temporal coexpression of interleukin 1 (IL-1) and its inhibitor, IL-1 receptor antagonist (IL-1ra), in the cervicovaginal fluid (CVF) beyond 24 weeks gestation including women in spontaneous term labor. Two cohorts of women were recruited at 24 to 35 weeks' gestation (n ¼ 65) and in late pregnancy (>36 weeks' gestation; n ¼ 88). The CVF was serially collected either every 4 weeks between 24 and 35 weeks' gestation (n ¼ 123 samples) or weekly during late pregnancy (n ¼ 240 samples). The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 48 publications
(81 reference statements)
3
35
0
2
Order By: Relevance
“…A positive fFN result may be confounded by other factors, including recent sexual intercourse, bleeding, digital vaginal examination and amniotic fluid contamination. Our previous studies have shown that recent unprotected sexual intercourse does not affect the expression of albumin (Liong S, Di Quinzio MKW, Fleming G, Permezel M, Georgiou HM, unpublished data), VDBP, 24 IL-1ra 12 or thioredoxin 11 in the CVF. A comprehensive systematic review of 27 published studies recently assessed the accuracy of fFN for the prediction of spontaneous preterm birth in symptomatic women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive fFN result may be confounded by other factors, including recent sexual intercourse, bleeding, digital vaginal examination and amniotic fluid contamination. Our previous studies have shown that recent unprotected sexual intercourse does not affect the expression of albumin (Liong S, Di Quinzio MKW, Fleming G, Permezel M, Georgiou HM, unpublished data), VDBP, 24 IL-1ra 12 or thioredoxin 11 in the CVF. A comprehensive systematic review of 27 published studies recently assessed the accuracy of fFN for the prediction of spontaneous preterm birth in symptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of IL-1ra and thioredoxin was based on our previously published observations relating to human parturition. [10][11][12] A summary of the obstetric characteristics of these 129 women and their respective sample numbers is presented in Supporting Information Table S3. Limited sample availability precluded the measurement of all four biomarkers in some cases.…”
Section: Validation Of Candidate Biomarkers Of Preterm Birthmentioning
confidence: 99%
“…This may be an explanation for miscarriages when this drug is used early during pregnancy. Apart from its physiological role in early pregnancy, IL1β may have some deleterious effects in late pregnancy (1). Along with IL1α, it may have play role in preterm labor, and serum levels may predict this (9).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 (IL-1), the blockade of which is a very attractive and rational primary treatment modality in various types of periodic fever syndromes as well as in cases of familial Mediterranean fever (FMF) resistant or intolerant to colchicine, is known to play physiological and pathological roles in early and late pregnancy, such as trophoblast motility and preterm labor, respectively (1). Pregnancy data with anti-IL1β agents are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that utilized mass spectrometry-based approaches have only identified peptides and proteins and not applied quantitative methods. To date, most studies that have attempted to characterize cervicovaginal fluid proteins have used samples obtained from pregnant and or laboring women [12][13][14] or in association with cervical cancer [15]. Such samples would be expected to display very different proteomes that those obtained from non-pregnant women.…”
Section: Introductionmentioning
confidence: 98%